Judges 'Consideration in the Decision of Fulfilling the Rights of Women and Children After Divorce in the Region of the DKI Jakarta High Religious Court - Abdurrahman Rahim (UIN Sunan Gunung Djati Bandung, 2020)
The background of this research is related to the most basic issues and has become the discourse among legal practitioners and academics so far, regarding how the rights of women and children that have been imposed by judges through their decisions can be implemented properly by ex-husbands voluntarily. In reality, in practice, many judges' decisions relating to women's rights are not carried out by ex-husbands. In addition, there is no mechanism that is able to ensure the payment of child and / or financial support by the defendant after divorce, ex-husbands are often absent from their obligations to pay for the rights of ex-wives and children after divorce. The results of this study indicate that: The position of guarantee for the rights of women and children after divorce is very weak, therefore the issue of living for wives who have been divorced by husbands and children still does not fully provide legal protection to wives. Judges' considerations in the decision of the Religious Court in the DKI Jakarta High Religious Court area in providing the rights of women and children in their development have attempted to provide protection in the form of charging fees as a result of divorce submitted by husbands to the Religious Court in the form of iddah, mut'ah, and livelihoods. children, common property